Forecasting of GRID Job Waiting Time from Imputed Time Series - Sutiene, K.; Vilutis, G.; Sandonavicius, D. (Elektronika ir Elektrotechnika, 2011)
Most attention in the paper is paid to GRID quality parameter, which specifies averaged time of execution of one job waiting in a cluster queue. Detailed analysis of time series of this parameter, which is received from monitoring systems of academic BalticGrid network, is presented. Seasonalities of variation of parameter value are shown graphically. Problematic forecasting cases of this parameter are reviewed. Forecasting methodology, which involves a model of data imputation, is proposed. The experiment is carried out, using forecasting methods that are prevailing in practice (AR, nAR, ARMA, SARIMA, CF technique). Ill. 10, bibl. 10, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.706